UPAYA PENCEGAHAN DIABETES MELLITUS DENGAN CEK GULA DARAH SECARA DINI PADA REMAJA PUTRI SEBAGAI CALON IBU BEBAS DARI PENYAKIT DIABETES MELLITUS - Astik Umiyah (P3M Universitas Aisyiyah Surakarta, 2024)
Diabetes mellitus is a non-communicable disease which is a serious threat to global and national health. This incident is increasing every year, not only regarding the elderly but even teenagers have detected diabetes mellitus. The purpose of this activity will be to examine the health conditions of diabetes mellitus and BMI, the two teenagers will receive consultations about health. The problem faced by adolescents is that they never know their health condition, because they think that there has never been a health problem that leads to diabetes mellitus. This activity will be carried out on the target of young female student respondents studying at the Faculty of Health Sciences with a total of 171 people. The data shows that most of the respondents are in their early to late teens. Nearly half of the respondents had prediabetes and most of the categories were not obese if the results of the Body Mass Index (BMI) were assessed. The conclusion from community service activities is that with an examination carried out early, diabetes mellitus can be identified and prevented earlier. The first step taken in preventing Diabetes Mellitus is by early detection of blood sugar on a regular basis and don't forget to exercise, eating arrangements can stabilize blood glucose and improve quality of life.